Effect of Trihoney (A Mixture of Trigona, Mellifera and Tualang) on Male Reproductive Hormones and Insulin Resistance in Hypercholesterolaemic Rabbits - Hamad Mohamed, Z; Ibrahim , M; Hamad Alfarisi, HA; Abdul Wahab , AY; Abd Fuaat, A; Che Mohamad, CA (IIUM Medical Journal Malaysia, 2020)
Introduction: Hypercholesterolaemia affects Sertoli and Leydig cells secretory functions, impairs steroid hormone biosynthesis, and disrupts the hypothalamic-pituitary-gonadal axis. The use of honey in previous studies resulted in an improvement of male reproductive hormonal disturbances. This study aimed to investigate the protective effects of Trihoney on hypercholesterolemia-induced male reproductive hormonal changes in male rabbits and compare its effects with atorvastatin. Materials and methods: Forty-eight male New Zealand white rabbits were assigned into 6 groups as follows; Control: commercial pellet; CH: commercial pellet with 0.6 g/kg/day Trihoney; HCD: 1% cholesterol diet; DH1: 1% cholesterol diet with 0.3 g/kg/day Trihoney; DH2: 1% cholesterol diet with 0.6 g/kg/day Trihoney and DAt: 1% cholesterol diet with 2mg/kg/day atorvastatin. After 12 weeks, the rabbits were sacrificed and blood samples were collected for analysis of hormones and pro-inflammatory cytokines and calculation of HOMA-IR. The testes were homogenized for intra-testicular testosterone measurement. Results: Serum testosterone reduced significantly in HCD (p<0.05) and DAt (p<0.05) groups. Likewise, intra-testicular testosterone reduced significantly in HCD (p<0.01) and DAt (p<0.01) groups. Serum FSH increased significantly in HCD (p<0.001) and DAt (p<0.01). Trihoney particularly at the dose of 0.6 g/kg/day improved serum and intra-testicular testosterone (p<0.05) and FSH (p<0.05). Trihoney and atorvastatin improved serum pro-inflammatory cytokines. Trihoney and atorvastatin did not affect HOMA-IR. Conclusion: Trihoney attenuated the detrimental effects of hypercholesterolaemia on male reproductive hormones which probably through a local effect on testicular tissue and Trihoney anti-inflammatory effect independent of insulin resistance. Atorvastatin did not counteract the impact of hypercholesterolaemia on the reproductive hormones.